Analysis of Factors That Influence MSME Tax Reporting Compliance with the Regulation of Government Facility Number 23-2018 During the Covid Era - Agustin, Irlaina; Safiq, Muhamad (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
The aims of this study is to determine the influence factor of the tax reporting compliance of MSME taxpayers with the regulation of government number 23 of 2018 during the covid-19 pandemic in order to fulfilling their tax obligations. The population of this research are the MSME that located in Bekasi Regency, registered as taxpayer on KPP Praatma Cibitung, KPP Pratama Cikarang Selatan, and KPP Pratama Cikarang Utara. The repondents in this study were 100 samples that collected using the purposive sampling by distributing questionnaire. Structural Equation modelling (SEM) is the method used to analyze the data obtained in this research. The result of this research prove that the tax rate is not influence the tax reporting compliance of MSME taxpayers on Bekasi Regency, meanwhile tax authorities’ service and tax knowledge had positive significant influence to tax reporting compliance of MSME taxpayers during covid-19 pandemic on Bekasi Regency.